Case epidemiology from the first three years of a pilot laboratory-based surveillance system for elevated blood-lead concentrations among children in England, 2014–17: implications for public health action. (24th May 2019) - Roberts, D J; Crabbe, Helen; Owodunni, Tayo; Gordon-Brown, Harriet; Close, Rebecca; Reshat, Shanel; Sampson, Barry; Ruggles, Ruth; Dabrera, Gavin; Busby, Araceli; Leonardi, Giovanni
Abstract: Background: Children incur lead toxicity even at low blood-lead concentrations (BLCs), and testing in England is opportunistic. We described epidemiology of cases notified to a passive laboratory-based surveillance system (SS), the Lead Poisoning in Children (LPIC) SS to inform opportunities to prevent lead exposure in children in England. Methods: Surveillance population: children <16 years of age and resident in England during the reporting period September 2014–17. Case definition: children with BLC ≥0.48 μmol/l (10 μg/dl). We extracted case demographic/location data and linked it with laboratory, area-level population and socio-economic status (SES) data. We described case BLCs and calculated age-, gender- and SES-specific notification rates, and age-sex standardised regional notification rates. Results: Between 2014 and 2017 there were 86 newly notified cases, giving an annual average notification rate of 2.76 per million children aged 0–15 years. Regionally, rates varied from 0.36 to 9.89 per million. Rates were highest in the most deprived quintile (5.38 per million), males (3.75 per million) and children aged 1–4 years (5.89 per million). Conclusions: Males, children aged 1–4 years, and children in deprived areas may be at higher risk, and could be targeted for primary prevention. Varied regional notification rates suggest differences in clinician awareness of lead exposure and risk factors; guidelines standardising the indications for BLC-testing may assist secondary prevention.